METHODS OF USING TOOTHPASTE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
From an early age, teeth need daily hygiene. In this article, we will talk about the role that toothpaste plays in oral hygiene. Let's find out what it consists of, what types of toothpastes there are and how to choose it correctly.